18F-FDG PET/CT in Multisystem Sjögren Syndrome. (May 2015) - Sharma, Punit; Chatterjee, Piyali
<x xml:space="preserve">Abstract</x> Abstract Sjögren syndrome (SS) is an autoimmune disease affecting exocrine glands, mostly lacrimal and salivary glands. Rarely, extraglandular sites such as skin, lung, kidneys, and nervous system may be involved. 18F-FDG PET/CT can be employed in SS for assessment of disease activity and for exclusion of lymphoma. We here present the case of a 61-year-old woman with SS where multisystem involvement was demonstrated on 18F-FDG PET/CT.